2012
DOI: 10.1186/1756-9966-31-87
|View full text |Cite
|
Sign up to set email alerts
|

Are there candidates for high-dose chemotherapy in ovarian carcinoma?

Abstract: BackgroundPrognosis of advanced ovarian carcinomas (AOC) remains poor with a 5-year survival of 30%. Benefit from high-dose chemotherapy (HDC) in this disease has not been demonstrated to date.MethodsTo evaluate the value of HDC as consolidation treatment after surgery and platinum/taxane-based therapy, we designed a monocentric retrospective comparative study. We used a subset approach to identify parameters associated with HDC efficacy.ResultsOne hundred and three AOC patients treated with conventional chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…More recently, a retrospective study ( 80 ) evaluated interest in the use of HDCT as consolidation therapy after surgery and taxane- and platinum-based therapy. In that study, 103 patients with advanced ovarian carcinoma were treated with conventional chemotherapy while 60 patients received HDCT with hematopoietic stem cell support.…”
Section: High-dose Chemotherapy To Treat Breast and Ovarian Cancermentioning
confidence: 99%
“…More recently, a retrospective study ( 80 ) evaluated interest in the use of HDCT as consolidation therapy after surgery and taxane- and platinum-based therapy. In that study, 103 patients with advanced ovarian carcinoma were treated with conventional chemotherapy while 60 patients received HDCT with hematopoietic stem cell support.…”
Section: High-dose Chemotherapy To Treat Breast and Ovarian Cancermentioning
confidence: 99%
“…Ferrandina et al . [22] and Sabatier et al [25] found that 67.3% and 59.2% of cases were of grade III, respectively. Others, found 50% of cases were of stage III, while Yoshikawa et al [26] reported 45.7% of cases were of stage I.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, as salvage therapy for refractory patients, high response rates were achieved with HDCT with stem cell support, although the response durations were short [16,17,18,19]. However, it is important to mention the fact that studies using HDCT for the treatment of ovarian cancer have contributed to show that not all patients are likely to benefit from such an approach [20,21]. …”
Section: Introductionmentioning
confidence: 99%